2020
DOI: 10.1021/acs.jpcc.0c01757
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Prediction of Methane Adsorption Isotherms at Varied Temperatures for Experimental Adsorbents

Abstract: Metal–organic frameworks (MOFs) are crystalline materials and one of the optimal materials for large-scale grand canonical Monte Carlo (GCMC) simulations. Recently, there have been trials for applying machine learning (ML) to the results of large-scale GCMC simulations to predict gas adsorption on MOFs. However, the functions of the developed algorithms are not different from those of GCMC simulations, in that they provide a prediction of adsorption properties based on the coordination structures. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…ML methods have already been successfully demonstrated for modeling physical and transport properties in various systems. Examples include predicting diffusion of organic compounds in air, binary gas mixtures, , organic compounds in water, and mixtures of binary solvents and hydrocarbons. , ML studies predicting lithium diffusion through solid-state membranes, activation energies for atomic diffusion on metal surfaces, , and ion transport in nanoparticle-based electrolytes have also been reported . Previous work from our group includes using ANNs and random forest methods to predict self-diffusion coefficients of both LJ fluids and real single component fluids. , We have also demonstrated that ANNs can be used to correct finite-size effects in MD simulations of self-diffusion and Maxwell-Stefan diffusion in binary LJ fluids .…”
Section: Introductionmentioning
confidence: 93%
“…ML methods have already been successfully demonstrated for modeling physical and transport properties in various systems. Examples include predicting diffusion of organic compounds in air, binary gas mixtures, , organic compounds in water, and mixtures of binary solvents and hydrocarbons. , ML studies predicting lithium diffusion through solid-state membranes, activation energies for atomic diffusion on metal surfaces, , and ion transport in nanoparticle-based electrolytes have also been reported . Previous work from our group includes using ANNs and random forest methods to predict self-diffusion coefficients of both LJ fluids and real single component fluids. , We have also demonstrated that ANNs can be used to correct finite-size effects in MD simulations of self-diffusion and Maxwell-Stefan diffusion in binary LJ fluids .…”
Section: Introductionmentioning
confidence: 93%
“…Machine learning has already been widely used for predicting gas adsorption in MOFs. To date, most of the reported machine models are limited to one single molecule or a specific pair of molecules, for instance, hydrogen, methane, nitrogen, CO 2 , and CO 2 /H 2 mixtures . Recently, broadening this list of molecules has generated interest while still focusing on small molecules and their mixtures. , Developing models that can rapidly be applied to very large and diverse collections of molecules (e.g., thousands of different species) represents a key means in which modeling could dramatically accelerate the scope of MOFs or similar materials for chemical separations in ways that cannot be accomplished experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…A small subset of molecular simulation data can be used to train a machine learning algorithm to screen materials quickly. Computational screening of MOFs has been successfully conducted for several applications. , Machine learning algorithms have been shown to have high accuracy and can significantly assist in identifying candidate materials faster and cheaper. , …”
Section: Introductionmentioning
confidence: 99%
“…16,17 Machine learning algorithms have been shown to have high accuracy and can significantly assist in identifying candidate materials faster and cheaper. 18,19 Because of the large number of potential MOFs, it is likely that there are high-performing materials that have yet to be discovered. There are various databases which are comprised of hypothetical materials that have been postulated, yet there are still more many more materials yet to be studied.…”
Section: Introductionmentioning
confidence: 99%